Clinical evaluation of the immediate effectiveness of GaAIAs laser on the therapy of dentin hypersensitivity (Journal of Applied Oral Science, 2004)
The aim of the present study was to determine the effectiveness of GaAlAs laser therapy with lambda670nm laser on the treatment of dentin hypersensitivity. Thirty-two intact human teeth were evaluated, the sensitivity of which to thermal (cold water), mechanical (probe) and evaporative (air) stimuli was recorded before and immediately after irradiation. Whenever desensitization was not observed after the first application, the patient was scheduled for a maximum of three further applications at 4-day intervals. The results demonstrated that laser therapy yielded a statistically significant reduction (p